UJI AKTIVITAS ANTIOKSIDAN DARI FRAKSI ETANOL, FRAKSI ETIL ASETAT, FRAKSI N-HEKSAN DAUN NIPAH (Nypa fruticans Wurmb.) - Husnani, Husnani (Jurnal Komunitas Farmasi Nasional, 2024)
Free radicals are ultraviolet rays that cause damage to the skin. Therefore, antioxidants are needed to prevent the dangers of free radicals in the body while repairing damaged body cells. One of the plants that contain compounds that have potential as antioxidants is nipah leaves. Previous research states that Nipah leaves have antioxidant activity with an IC50 value of 9.662 ppm with a very strong category, so this study aims to determine the antioxidant activity of the ethanol fraction, ethyl acetate fraction and n-hexane fraction, and determine which fraction can provide the strongest antioxidant activity value. The methods used in this study include preparation of simplisia, preparation of nipah leaf fractions, phytochemical screening of fractions, antioxidant activity test of nipah leaf fractions using DPPH method.